Strategi Meningkatkan Kepuasan Dalam Membentuk Perilaku Nasabah Pada Lembaga Keuangan Perbankan Di Jawa Tengah - Siti Fatonah; Yuniatin TDKW (Universitas Sahid Surakarta, 2019)
This study aims to determine the effect of service quality, image and relationship marketing on satisfaction and its impact on customer behavior in shaping loyalty to financial institutions in Central Java. Sampling in this study using the Random sampling technique. The number of samples taken in this study is as many as 100 respondents who are customers of Banking Financial Institutions in Central Java. The analytical tool used is the research instrument test, linearity test, path analysis and regression with t test, F test and R2 test. T test results show that service quality, image and relationship marketing have a positive effect on customer satisfaction. And service quality, relationship marketing and satisfaction have a positive effect on customer behavior. While the image has a negative effect on customer behavior. The results of direct and indirect effects can be concluded that the satisfaction variable as an intervening variable service quality and relationship marketing is ineffective, and more effective service quality and relationship marketing directly affects customer behavior in shaping loyalty to the Central Java Regional Financial Institution. And while the Image variable is more effective in influencing customer behavior if it is through satisfaction as an intervening variable. Whereas for the direct path of Relationship Marketing towards behavior is the most dominant and most effective way to improve customer behavior to be loyal to the Banking Financial institution, because it has the highest regression coefficient value.